Perilaku Biaya Asimetris Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia - Jems Arison Zacharias (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This research was conducted to examine the of asymmetric costs behaviour in banking companies listed on the Indonesia Stock Exchange (IDX), especially sticky costs on administrative and general expenses and anti-sticky costs on interest expenses. The method used to test the research hypothesis is multiple linear regression analysis with the Anderson, Banker, Janakiraman (ABJ) model. The population for this study were all banking companies listed on the IDX and the sample selection was carried out using a purposive sampling method with an observation period during the 2018-2021 period. The results of the study show that sticky costs occur in administrative and general expenses in banking companies in which the rate of increase of general and administrative expenses when income increases are much greater than the rate of decrease in the equivalent amount. Meanwhile, anti-sticky cost behaviour occurs in interest expenses in banking companies in which the magnitude of the increase in administrative and general expenses when income increases is much smaller than the magnitude of the rate of decrease in an equivalent amount. The results of this study are in accordance with the theory of cost adjustments and managerial decisions in which managers will adopt policies that can provide the best profit with the smallest risk for banks when making adjustments to resources and costs that are sticky.